Autoregressive Integrated Moving Average Predictive Modelling for Per Capita GDP of Nepal - Chand, Dipendra Bahadur (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
A nation's Gross Domestic Product (GDP) is an important index that reflects the health and performance of an economy and its aggregate income. In this paper, annual data of Nepal's GDP for the period 1960 – 2022 is used to forecast the GDP of Nepal through Autoregressive Integrated Moving Average (ARIMA) modelling techniques. We seek to make accurate long-term predictions for the period 2023 – 2037 to gain insights into the future expected trajectory of economic growth in Nepal. In the present empirical study, stationarity at the second-order differencing with the ARIMA (2, 2, 1) model is identified to predict the GDP of Nepal for the next 15 years. The finding shows that the forecast values of Nepal’s GDP will be 1384.426 per capita in 2023 and 2180.822 per capita in 2037. Our study provides skeletal guidance for government bodies and investors who rely on planning and strategizing resources on accurate predictions of GDP per capita. By accurately predicting GDP per capita, administrators in investment and policy making can make informed economic decisions that may steer economic growth, stability, and development in an optimum direction.